First reactions and future expectations of parents of children with developmental disabilities - Rashikj Canevska, Olivera; Chichevska Jovanova, Natasha; Troshanska, Jasmina; Ramadani Rasimi, Teuta; Dimitrovska, Kristina (Edukcisko-rehabilitaciski fakultet u Zagrebu, 2024)
The birth of a child in the family is usually a period filled with joy and the formation of new feelings such as immense happiness, pride, self-realisation, success, and confirmation of identity. However, the birth of a child with developmental disabilities represents a strong challenge and a threat to the disruption of family life. The main aim of this study was to examine the reactions and feelings of parents as part of a family unit with a child with special needs. Several stress factors, positive and negative emotions, impact of disability on family members, and expectations for the future were investigated. Data were collected by surveying a group of 77 respondents who were parents of children with developmental disabilities. The results of this research indicate that, although all parents faced similar challenges, emotions, and struggle with similar problems, to a large extent the emotions that dominated, the time needed to accept reality, and the challenges they faced were directly associated with the type of disability of the child. A total of 52% of respondents experienced some changes in marital relations after the arrival of a child with a disability in the family, 45.5% of respondents answered that someone from the family was forced to leave the workplace, 49.35% of parents answered that they neglected their own social life, and 51.94% of parents pointed out that the biggest challenge they were currently facing was psychological stress. In fact, parenting a child with a disability can present a unique and complex set of challenges.
Keywords: disabilities, families, first reactions and expectations